Paroxysmal Atrial Fibrillation in Elderly: Worldwide Preliminary Data of LINAC-Based Stereotactic Arrhythmia Radioablation Prospective Phase II Trial - Di Monaco, Antonio; Gregucci, Fabiana; Bonaparte, Ilaria; Troisi, Federica; Surgo, Alessia; Di Molfetta, Domenico; Vitulano, Nicola; Quadrini, Federico; Carbonara, Roberta; Martinelli, Gaetano; Guida, Pietro; Ciliberti, Maria Paola; et al. (Frontiers in Cardiovascular Medicine, 2022)
Treatment approach for elderly patients with atrial fibrillation (AF) is difficult. The present prospective phase-II trial evaluated LINAC-based stereotactic arrhythmia radioablation safety in this population. The reported data of the first 5 patients worldwide, showed no side effects, absence of AF episodes and without antiarrhythmic drugs. Trial Registration: ClinicalTrials.gov, identifier: NCT04575662.